A Numerical Study of Gravity Waves Propagation Characteristics in the Mesospheric Doppler Duct. Issue 13 (6th July 2021) - Dong, Wenjun; Hickey, Michael P.; Zhang, Shaodong
Abstract: Dong et al. (2018, https://doi.org/10.1029/2018JD029190, hereafter D18) employed a compressible model to examine the long‐distance horizontal propagation of gravity waves (GWs) in a stratospheric thermal duct in a two‐dimensional domain. Here, we extend this previous work to explore the ducting of GWs in the mesospheric Doppler duct. While most of the characteristics of the thermal duct described in D18 are found to be operative in the Doppler duct, there are some important differences. The propagation velocity of the fundamental (0th) wave mode is always largest in the Doppler duct and smallest in the thermal duct. We find that regardless of the type of duct (Doppler or thermal duct) the energy dissipation rates of wave modes in the duct region are inversely proportional to their horizontal group velocities. Our results suggest that observations of ducted GWs, particularly those made from multiple observation sites, should reveal characteristics that are germane to the particular duct type. For example, we find that the frequency of the dominant wave mode in the Doppler duct increases with increasing distance from the wave source. This behavior is exactly the opposite of what was obtained for the thermal duct by D18. Key Points: Simulations show that the propagation velocity of the 0th wave mode is always largest in the Doppler duct and smallest in the thermal duct Observations of ducted gravity waves those made from multiple observation sites should reveal characteristics that are germane to the duct type The energy dissipation rates of wave modes in the duct region are inversely proportional to their horizontal group velocities